Assessing User Acceptance on Competencies Level Assessment System using Technology Acceptance Model - Zuraini Hanim Binti Zaini, Zuraini Hanim (Universiti Teknologi PETRONAS, 2008)
This project is aims to prove the idea of implementing the Competencies Level Assessing System (CLASS) for training center by using the Technology Acceptance Model (TAM). The CLASS system using Weighted scoring model approach to calculate the Competencies Level of the training session The system able to produce the details performance of the respondent and generate the recommendation for each respondent.Technology Acceptance Model (TAM) that focus on the usefulness of the system is using to evalutes the user’s acceptance on the implementing the CLASS system The data gathered analyzed using t-test analysis.